Litigating in the Time of Coronavirus: Mental Health Tribunals’ Response to COVID-19 - Dhand, Ruby; Szigeti, Anita; Kotob, Maya; Kennedy, Michael; Ye, Rebecca (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2020)
People with mental health and addiction issues are disproportionately affected by COVID-19 given the elevated risk of contracting COVID-19 within psychiatric facilities. The impact of the pandemic on this extraordinarily vulnerable population includes the potential for large outbreaks and multiple deaths. There is also the increased risk of serious psychological harm, exacerbating pre-existing mental health and substance use issues and in turn elevating their risk to themselves and/or others. In Part I of this paper, we analyze the procedural barriers to access to justice that arose as a result of the initial responses to COVID-19 by the Consent and Capacity Board [CCB] and the Ontario Review Board [ORB]. In Part V, we include a brief report on how appeals taken from both tribunals have been handled throughout COVID-19 to date. In Part VI, we analyze the discretionary and systemic barriers experienced by people with mental health and addiction issues appearing before the CCB and ORB during COVID-19. We critique recent mental health law cases during COVID-19 where deprivations of liberty interests and substantive equality have occurred, and access to justice for people with mental health and addictions issues has been denied, suspended or impaired. Through a legal analysis of how the pandemic has impacted this vulnerable community of litigants, we hope this research will result in further advocacy and education to prevent outbreaks and death, improve health care practices, and increase access to justice.